Evaluasi Daya Dukung Pondasi Tiang Pancang Pada Gedung Universitas Muhammadiyah Lamongan - Hutasoit, Eva Olivia; Rizkiyah, Awaliatul (Jurnal Teknik Sipil, 2023)
The pile foundation is a deep foundation that is often used in the construction of high-rise buildings and small-scale buildings. The foundation is required to have a greater bearing capacity than the load on it. This study aims to determine the maximum bearing capacity of the foundation against the work load including the additional load from the 15-story Lamongan Muhammadiyah University building which was found to be cracked. Calculation of the bearing capacity of a single pile is carried out to determine the bearing capacity of a single pile using the Mayerhoff, Reese O'neil, and Reese and Wright method. Calculation of the bearing capacity of group piles is carried out to determine the bearing capacity of piles in one group using the Converse-Labarre, Los Angle Group, and Seiler-Keeney methods. Controlling the bearing capacity of single and group pile foundations, whether they are able to withstand the load on them using the axial loads and moments obtained. The results of the calculation of the bearing capacity of a single pile foundation at a depth of 30 m using the Meyerhoff calculation method obtained the carrying capacity of a single pile permit (Q_a) at point DB-1 of 916,80 tons and DB-2 of 916,80 tons, Reese and O' neil obtained Power single pile permit bearing (Q_a) at point DB-1 of 668,67 tons and DB-2 of 668,67 tons, Reese and Wright obtained single pile permit bearing capacity (Q_a) at point DB-1 of 1.070,08 tons and a DB-2 of 1.070,08 tons, while the shamanic strength of the largest pile group foundation was obtained using the Converse-Labarre method with ultimate bearing capacity using the Reese anad Wright method, bearing configuration from the pile group capacity (Q_g) (2 x 2) obtained at point DB -1 of 9.733,45 tons and DB-2 of 9.733,45 tons, configuration (2 x 3) at point DB-1 of 13.810,45 tons and DB-2 of 13.810,45 tons, configuration (3 x 2 ) at point DB-1 of 13.810,45 tons and DB-2 of 13.810,45 tons. The results of controlling the bearing capacity of the foundation by looking at the value of the allowable bearing capacity is greater than the value of the axial load (P ≤ Q_g). From the calculation of the bearing capacity of the piles it can be concluded that the pile foundations at points DB-1 and DB-2 are safe.